ANALYSIS OF EXTERNAL ENGINEERING NETWORK METHODS: Array - Zhvan, V.; Donenko, І.; Kulish, S.; Taran, А. (Municipal economy of cities. Series: «Economy science», 2020)
The article is devoted to the effective analysis of trench and trenchless pipeline laying technologies. In the course of the work, an analytical review of pipeline assembly was performed, the main technological parameters, the scope of each method, and their advantages and disadvantages were determined. List of considered pipeline laying methods: trenching, horizontal directional drilling, mechanical puncture, hydraulic puncture, microtunneling and punching. The article analyzes the classical trench method and the most widely used trenchless ones: horizontal directional drilling; mechanical puncture; hydraulic puncture; microtunneling; punching. Each of these methods has several advantages and disadvantages. The choice of the optimal method of laying the pipeline depends on many factors: the physical and mechanical properties of soils and hydrogeological conditions, the length and diameter of the pipeline, the presence of other communications, buildings and structures, as well as the budget that customers have. Work time is the last deciding factor. Based on the results of the analysis of pipeline laying technologies and expert survey of construction industry experts, the cost table of each method was compiled, outlining the main characteristics of the technology: length of pipeline, speed of work, scope, cost, and the advantages and disadvantages of each of the considered methods. The conclusions about the use of each of the pipeline laying methods were made. Each of the methods has its advantages and disadvantages, so to choose the method of work it is necessary to conduct a comprehensive assessment of technological parameters, cost, scope and timing of work. The cost of laying the pipeline consists of the following factors: conducting research; selection of diameter and determination of pipeline length; choice of laying method and equipment necessary for the works; selection of equipment, shut-off and control equipment and other materials arranged on the pipeline; terms of performance of works. Taking into account these factors, an estimate is made, which determines the cost of installation of a particular pipeline. After the analysis, we can conclude that among the methods of trenchless laying of pipelines can be identified horizontally directional drilling, it is this method of laying the pipeline will be appropriate to use for our region. The drilling technique allows to carry out pipelines under obstacles, to pull long segments of networks, to repair site damage. This method is universal and can be used in almost any environment.